Improving Meetings with Microphone Array Algorithms - Tashev, Ivan (Machine Learning Meets the User Interface Workshop, Neural Information Processing Systems NIPS 2003, 2003)
Beamforming is ability to make the microphone array to listen to given location, suppressing the signals coming from other locations. Electronically steerable. A slideshow on Microphone Array.